An evaluation of self-perceived knowledge, attitudes and behaviours of UK oncologists about LGBTQ+ patients with cancer. Issue 6 (18th November 2020) - Berner, Alison May; Hughes, Daniel Johnathan; Tharmalingam, Hannah; Baker, Tom; Heyworth, Benjamin; Banerjee, Susana; Saunders, Daniel
Abstract : Introduction: Over one million people in the UK identify as LGBTQ+ (lesbian, gay, bisexual, transgender, queer or questioning). Research has shown that this population experience differing cancer risk factors compared with non-LGBTQ+ patients and persistent inequalities in cancer care. Literature concerning the knowledge of oncologists of this group's healthcare needs is limited; our study aimed to evaluate knowledge, attitudes and behaviours of UK oncologists about LGBTQ+ patients. Methods: A 53-question survey was delivered via a secure online platform. Questions covered respondent demographics, knowledge, attitudes and behaviours with the majority of responses on a Likert scale. Oncologists were recruited via email from professional bodies and social media promotion. Informed consent was sought and responses fully anonymised. Multifactorial ordinal logistic regression and Fisher's exact test were used to assess for interactions between demographics and responses with Holm-Bonferroni multiple testing correction. Results: 258 fully completed responses were received. Respondents had a median age of 43 years (range 28–69); 65% consultants and 35% registrars; 42% medical, and 54% clinical, oncologists. 84% felt comfortable treating LGBTQ+ patients but only 8% agreed that they were confident in their knowledge of specific LGBTQ+ patient healthcare needs. There were low rates of routine enquiry about sexual orientation (5%), gender identity (3%) and preferred pronouns (2%). 68% of oncologists felt LGBTQ+ healthcare needs should be a mandatory component of postgraduate training. Conclusions: This survey showed that UK oncologists feel comfortable treating LGBTQ+ patients but may fail to identify these patients in their clinic, making it more difficult to meet LGBTQ+ healthcare needs. There is self-awareness of deficits in knowledge of LGBTQ+ healthcare and a willingness to address this through postgraduate training. Educational resources collated and developed in accordance with this study would potentially improve the confidence of oncologists in treating LGBTQ+ patients and the cancer care these patients receive.